2011
DOI: 10.1016/j.freeradbiomed.2011.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Nectarine promotes longevity in Drosophila melanogaster

Abstract: Fruits containing high antioxidant capacities and other bioactivities are ideal for promoting longevity and healthspan. However, few fruits are known to improve the survival and healthspan in animals, let alone the underlying mechanisms. Here we investigate the effect of nectarine, a globally consumed fruit, on lifespan and healthspan in Drosophila melanogaster. Wild-type flies were fed the standard, dietary restriction (DR) or high fat diets supplemented with 0–4% nectarine extract. We measured lifespan, food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 64 publications
(103 reference statements)
2
44
0
Order By: Relevance
“…Thus, resveratrol uptake should not be much different among these three diets. On the other hand, we previously demonstrated that female flies on the DR and high-fat diets increased food intake in volume by about twofold, when compared to those on the standard base diet (Zeng et al 2011;Boyd et al 2011). Thus, flies ingested about twofold more resveratrol on the DR or high-fat diet, when compared to the base diet with the same concentration of resveratrol.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Thus, resveratrol uptake should not be much different among these three diets. On the other hand, we previously demonstrated that female flies on the DR and high-fat diets increased food intake in volume by about twofold, when compared to those on the standard base diet (Zeng et al 2011;Boyd et al 2011). Thus, flies ingested about twofold more resveratrol on the DR or high-fat diet, when compared to the base diet with the same concentration of resveratrol.…”
Section: Discussionmentioning
confidence: 84%
“…Fly stocks were routinely maintained on standard fly cornmeal agar medium at 25±1°C, 60± 5% humidity, and a 12-h light/dark cycle (Ashburner et al 2005). Five types of sugar-, yeast extract-, and palmitic acid-based diets as control diets were prepared as previously described (Boyd et al 2011). The standard base diet contained 10% sugar and 10% yeast extract in weight/volume; the DR diet had 2.5% sugar and 2.5% yeast extract; the high sugar-low protein diet consisted of 18% sugar and 2% yeast extract; the low sugar-high protein diet contained 2% sugar and 18% yeast extract; and the high-fat diet had 10% sugar, 10% yeast extract, and 2% palmitic acid.…”
Section: Fly Strains and Culture Conditionsmentioning
confidence: 99%
See 3 more Smart Citations